A new, high‐precision CA‐ID‐TIMS date for the 'Kalkberg' K‐bentonite (Judds Falls Bentonite). (16th September 2017) - McAdams, Neo E.B.; Schmitz, Mark D.; Kleffner, Mark A.; Verniers, Jacques; Vandenbroucke, Thijs R.A.; Ebert, James R.; Cramer, Bradley D.
Abstract : The numerical calibration of the base of the Devonian is poorly constrained due to several factors. Few precise radioisotopic age determinations are available from the late Silurian and Early Devonian, and the limited published data carry large error bars from older analytical methodologies. Volcanic ashfalls suitable for dating occur in the Lower Devonian of the Appalachian Basin, but have not been precisely correlated into the global chronostratigraphical scheme because of limited bio‐ and lithostratigraphical information. Here, we report a new U‐Pb zircon radioisotopic age determination of 417.61 ± 0.12(0.23)[0.50] Ma and improved chronostratigraphical context, including revised biostratigraphy, for an ash bed in the New Scotland Formation, Helderberg Group, from the Lochkovian Stage that was previously identified as the Kalkberg K‐bentonite. This new information helps to integrate the classic New York Appalachian Basin succession into global Siluro‐Devonian stratigraphy, refine the calibration of the Silurian–Devonian boundary and more precisely estimate the duration of both time periods.